New and future developments in microbial biotechnology and bioengineering : from cellulose to cellulase. Strategies to improve biofuel production - Srivastava, Neha; Srivastava, Manish; Mishra, P. K. (Pradeep Kumar); Ramteke, P. W.; Singh, Ram Lakhan (Elsevier, 2019)
New and Future Developments in Microbial Biotechnology and Bioengineering: From Cellulose to Cellulase: Strategies to Improve Biofuel Production outlines new methods for the industrial production of the cellulose enzyme. The book compares the various processes for the production of biofuels, including the cost of cellulose production and availability. Biofuels are considered to be the main alternatives to fossil fuels in reducing environmental pollution and climate change. Currently, all existing biofuel production is suffering because of the high costs of production processes. As a result, cost effective practical implementation is needed to make this a viable energy alternative.